The Changing Exploitation of Oysters (Ostrea edulis L. 1758) in Late Medieval and Early Modern England: A Case Study from Dudley Castle, West Midlands. (2nd January 2020) - Thomas, Richard; Law, Matt; Browning, Emma; Hill, Alistair; Small, Rachel
ABSTRACT: Analysis of over 4000 complete left oyster valves from late medieval and post-medieval Dudley Castle reveals the changing role of this perishable luxury over a 700-year period. Throughout the occupation, it seems that oysters were used as ingredients rather than served raw in the shell. A greater reliance on oyster consumption is apparent in the later fourteenth century, perhaps reflecting a more diverse diet amongst the aristocracy in the wake of the Black Death. An increased preference for mussels and whelks is also attested in the Tudor and early modern periods, reflecting changing perceptions of these foods. Overall, it is likely that natural beds were exploited throughout the time that oysters were being brought to Dudley Castle; however, the evidence demonstrates a shift from limited exploitation of natural inter-tidal sources in the eleventh century towards the dredging of sub-littoral beds in later periods, with some possible translocation of oyster stock. Changes in the shape, size and appearance of the oyster shells suggest the source locales from which the oysters derived changed through time. A notable shift occurred in the fourteenth century, which could reflect changes in supply brought about by altered tenancy at Dudley Castle and/or disruptions to trade brought about by the Black Death. Future biochemical analyses are recommended to provide greater clarity on the origin of those sources.